ChemInform Abstract: A Concise Synthesis of Sugar Isoxazole Conjugates. Issue 7 (18th February 2014) - Luginina, Jevgenija; Rjabovs, Vitalijs; Belyakov, Sergey; Turks, Maris
Abstract This provides the first examples of isoxazolyl sugars where the azole fragment is attached to C3 of the carbohydrate through a C—C bond.